2000
DOI: 10.1054/bjoc.2000.1418
|View full text |Cite
|
Sign up to set email alerts
|

Protracted venous infusion 5-fluorouracil in combination with subcutaneous interleukin-2 and alpha-interferon in patients with metastatic renal cell cancer: a phase II study

Abstract: Our purpose was to assess the activity of alpha-interferon (IFN-α), interleukin-2 (IL-2) and 5 fluorouracil (5FU) administered by protracted venous infusion (PVI) as opposed to bolus injection. 55 patients with advanced renal cell cancer were treated as follows: IL-2 and IFN-α according to the schedule originally described by Atzpodien, with PVI 5FU 200 mg m–2 day–1 during weeks 5–9. 42 patients (76%) were of moderate or poor prognosis as defined by previous studies. The response rate by intention to treat was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(12 citation statements)
references
References 24 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…This protocol is closely related to the schedule designed for other clinical research trials with IL-2, IFNa and 75-FU within the framework of the French Immunotherapy Group Négrier et al, 2000). These large studies showed an unexpectedly low response rate Négrier et al, 2000) like the present study, compared to more promising results obtained by others (Atzpodien et al, 1993;Hofmockel et al, 1996;Joffe et al, 1996;Ellerhorst et al, 1997;Tourani et al, 1998;Allen et al, 2000;Dutcher et al, 2000;Elias et al, 2000;van Herpen et al, 2000).…”
Section: Discussionsupporting
confidence: 67%
“…This protocol is closely related to the schedule designed for other clinical research trials with IL-2, IFNa and 75-FU within the framework of the French Immunotherapy Group Négrier et al, 2000). These large studies showed an unexpectedly low response rate Négrier et al, 2000) like the present study, compared to more promising results obtained by others (Atzpodien et al, 1993;Hofmockel et al, 1996;Joffe et al, 1996;Ellerhorst et al, 1997;Tourani et al, 1998;Allen et al, 2000;Dutcher et al, 2000;Elias et al, 2000;van Herpen et al, 2000).…”
Section: Discussionsupporting
confidence: 67%
“…This biological response modifier is currently employed in the management of metastatic melanoma and renal cell carcinoma, alone or in combination with chemotherapy or biotherapy [18][19][20][21].…”
Section: Biotherapeutic Agentsmentioning
confidence: 99%
“…However, some patients have good quality responses with prolonged disease-free survival, and for this reason immunotherapy has remained the standard first-line treatment for this disease (Medical Research Council Renal Cancer Collaborators, 1999). Combinations of immunotherapy and 5-fluorouracil (5-FU) chemotherapy have produced consistently higher response rates of 20 -39% in previously untreated patients, but at the expense of additional toxicity Lopez Hanninen et al, 1995;Tourani et al, 1998;Allen et al, 2000;van Herpen et al, 2000). As yet there is no randomised evidence supporting the superiority of this approach over standard immunotherapy.…”
mentioning
confidence: 99%